Moral institutions and evolution: In search of equilibria - Martin Alois Leroch (Hochschule Pforzheim, 2022)
After having met severe opposition with its introduction, evolutionary ethics is becoming increasingly popular. One adherent is Ken Binmore, who - extremely simplified - argues that evolution has equipped humans with the inclination to reciprocate, and that via reciprocity moral norms have evolved. While Binmore's theory more or less implicitly rests upon several behavioral assumptions, it lacks a clear empirical foundation. In this paper, I provide a summary of key results from various disciplines related to the core assumptions, namely: i) People behave as if they held other-regarding preferences, ii) Such other-regarding behavior is enforced via reciprocity, iii) Norm-violators are punished, and iv) In the absence of norms, people employ a trial-and-error strategy from which an equilibrium will evolve. While most of these assumptions are well-supported, the application of equilibria to real-world states of the world seems problematic. Rather, human behavior is heterogenous and in constant flux. Further, because morality is merely one institution embedded in a wider set of institutions, the evolutionary pressure does not influence moral norms in isolation. If one institution changes, so will the (theoretical) equilibrium of the institution "morality".
Keywords: 330